P014 Shift work disorder and the prevalence of help seeking behaviours for sleep concerns in Australia. (7th October 2021) - Brown, B; Crowther, M; Appleton, S; Melaku, Y; Adams, R; Reynolds, A
Abstract: Introduction: Shift work disorder is a circadian rhythm sleep-wake disorder, defined by symptoms of insomnia and excessive levels of sleepiness resulting from work that occurs during non-standard hours. Sleep problems are common in shift workers, yet our understanding of help-seeking behaviours for sleep in shift workers is limited. Methods: As a part of a national sleep health survey, data were collected on the help-seeking behaviours for sleep problems in an online sample of Australian individuals on non-standard work schedules (n=448). Of the sample of non-standard workers, 10.5% (n=41) met the criteria for probable shift work disorder (pSWD). Results: Non-standard workers with pSWD did not seek help for sleep problems at higher rates than workers without SWD (p = .979). General practitioners were the most reported healthcare professional sought out for sleep problems of individuals with pSWD. Self-management was common in workers with pSWD, with a high self-reported prevalence of alcohol use (31.7%) as a sleep management strategy, and caffeine consumption (76.9%) as a sleepiness management strategy. The majority of individuals with pSWD reported the mentality of 'accept it and keep going' as a sleepiness management strategy, highlighting a potential barrier to help-seeking behaviour in workers with pSWD. Discussion: These findings provide novel insight into the help-seeking behaviours of individuals with pSWD. There is a need for further research to understand why individuals at risk for shift work disorder are not actively seeking help, and to develop health promotion and intervention strategies to improve engagement with healthcare professionals.